1999
DOI: 10.1021/jp990998o
|View full text |Cite
|
Sign up to set email alerts
|

Rate Coefficient Measurements of the Reaction CH3 + O2 = CH3O + O

Abstract: Rate coefficients for the reaction CH3 + O2 = CH3O + O were measured behind reflected shock waves in a series of lean CH4−O2−Ar mixtures using hydroxyl and methyl radical diagnostics. The rate coefficients are well represented by an Arrhenius expression given as k = (1.6 ) × 1013 exp(−15813 ± 587 K/T) cm3 mol-1 s-1. This expression, which is valid in the temperature range 1575−1822 K, supports the downward trend in the rate coefficients that has been reported in recent determinations. All measurements to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
(75 reference statements)
3
35
0
Order By: Relevance
“…Low-pressure rate constants for Ar and N 2 as collisional partners [38][39][40]42] are very close, confirming the uncertainty factor evaluated by Troe [38]. Recent measurements of Hwang et al [43] for Ar within 950-1200 K are also in close agreement with Mueller et al [39]. The measurements of Ashman and Haynes [41] are systematically higher than that of Mueller et al [39]; however, Scire et al [44] concluded that they overlap, taking into account significant uncertainty in the determination of rate constants using complex reaction mechanisms.…”
Section: Reaction Mechanismsupporting
confidence: 67%
“…Low-pressure rate constants for Ar and N 2 as collisional partners [38][39][40]42] are very close, confirming the uncertainty factor evaluated by Troe [38]. Recent measurements of Hwang et al [43] for Ar within 950-1200 K are also in close agreement with Mueller et al [39]. The measurements of Ashman and Haynes [41] are systematically higher than that of Mueller et al [39]; however, Scire et al [44] concluded that they overlap, taking into account significant uncertainty in the determination of rate constants using complex reaction mechanisms.…”
Section: Reaction Mechanismsupporting
confidence: 67%
“…Although Troe [66] estimated a reliability of his recommended rates to be about 20%, the discrepancy between different experimental data [70][71][72][73][74][75] and new expressions proposed and implemented by Shimizu et al [43], Burke et al [33] and Keromnes et al [22] is still about 30-40% as illustrated in the Supplemental material (Figs. S1-S5).…”
Section: Reactionsmentioning
confidence: 94%
“…The line summarizing the present results, eq 5, is plotted in Figure 11. In the past decade, there are four additional studies 3,5,11,55 to which the present reanalysis can be compared. Hwang et al, 5 Herbon et al, 11 and Naumann 55b have reported respective values of …”
Section: Figurementioning
confidence: 99%